Design Considerations for Augmented Reality Supported Tactical Decision Making Systems - Smarr, Simone A.; Davis, Alexis; Traynham, Niya; Abram, Nicholas; Aryal, Saurav K.; Nias, Jaye; Williams, Lucretia; Blackstone, Jeremy; Washington, Gloria (Proceedings of the AAAI Symposium Series, 2026)
In high-stakes environments, tactical decision making is critical, and managing cognitive load and stress is important. The Tactical Decision Making Under Stress (TADMUS) program established a foundation for decision-support systems grounded in naturalistic decision-making processes and meaningful information presentation. Immersive technologies, like augmented reality (AR), create opportunities to extend this work while introducing new design challenges related to cognitive load and awareness. This research explores the design of an AR decision support interface for TADMUS contexts using a human-centered design approach informed by alert design, augmented reality, and decision support literature. Focused on alert systems as a key mechanism for communicating time-sensitive information in spatial computing environments, we identify AR-specific alert design challenges that should be considered and present a tiered alerting approach to support tactical decision making.